Nível e compreensão do estigma em pessoas acometidas pela hanseníase no município de Fortaleza-Ce - Silva, Patrícia do Nascimento (2023)
Leprosy is part of a group of diseases caused by infectious agents or parasites called neglected tropical diseases. For a long time it was considered an incurable disease and its sufferers unworthy of social life, which led to compulsory segregation and isolation. This stigma can directly interfere with social life, work and interpersonal relationships, which can lead to stress and emotional suffering. The objective was to evaluate the level of stigma and its understanding in people affected by leprosy in the city of Fortaleza - CE. This is a cross-sectional, descriptive and analytical study, with quantitative and qualitative approaches. Data collection was divided into two stages. Stage one is quantitative in nature, with sociodemographic characterization and level of stigma of people affected by leprosy, stage two is qualitative, with the understanding of stigma in people who scored above zero in stage one. To carry out the interview, a script was created, containing seven dimensions, based on questions from the EMIC-AP scale. To analyze the quantitative data, univariate analysis of sociodemographic variables was used. In the qualitative analysis, the second thematic analysis modality was used. Among those evaluated in stage one (n= 100), 66% were men, 67% declared themselves to be of mixed race, 56% were concentrated in the age group of 40 to 59 years old. The dominant marital status was stable union (29%). When it comes to education, incomplete primary education stood out (24%). Regarding their current work situation, part of the sample reported being inactive (34%). Regarding the level of stigma, 88 participants had a score above zero, these being the ones who were invited to participate in stage two of this study. In stage 2, 27 people were interviewed, of which 51.8% were men, aged between 20 and 66 years, 70.3% classified as multibacillary (MB). The predominant clinical form was dimorphic with 40.8%. 29.6% had some type of physical disability. 40.8% had leprosy reactions. Regarding family cases, 14.9% of participants stated that they had cases of leprosy in the family. After applying the script, it was seen that the seven dimensions were covered, emerging feelings such as: sadness, fear, shame, withdrawal, change in behavior, anger, indifference, among others. It was possible to observe in the interviewees' statements that participants with PB leprosy had a lower level of self-stigma and a higher level of coping and overcoming, highlighting the importance of an early diagnosis. The qualitative approach to understanding stigma, based on the script constructed in this study, allowed us to understand the affected dimensions, understanding the stigma experienced, and with this, care can be guided in a more comprehensive and individualized manner.